Skin manifestations of pancreatic diseases - Kunovský, Lumír; Dítě, Petr; Březinová, Eva; Sedláková, Libuše; Trna, Jan; Jabandžiev, Petr (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2022)
Although symptoms of pancreatic diseases such as pancreatitis, acute and chronic and, carcinoma of the pancreas are mainly gastrointestinal in nature, the extra-pancreatic symptoms are also important. These include skin symptoms, such as pancreatic panniculitis, acanthosis nigricans, livedo reticularis, necrolytic migratory erythema, cutaneous signs of hemorrhage, as in persons with severe acute pancreatitis, or the finding of cutaneous metastases of pancreatic carcinoma, which may be a sign of advanced disease. The pancreas is therefore one of those organs for which diagnosis and therapy are often multidisciplinary. In this review article, we summarize current knowledge of the possible skin manifestations of pancreatic disorders.
Keywords: Pancreatitis; Pancreatic Neoplasms; akutní nemoc; kožní nemoci; lidé; Acute Disease; pankreatitida; Pancreatic Diseases; nádory slinivky břišní; Skin; kůže; Skin Diseases; nemoci slinivky břišní; Humans